The alginate regulator AlgR and an associated sensor FimS are required for twitching motility in Pseudomonas aeruginosa. - Whitchurch, C B (1996)
Mucoid strains of Pseudomonas aeruginosa isolated from the lungs of cystic fibrosis patients produce large amounts of the exopolysaccharide alginate. AlgR has long been considered a key regulator of alginate production, but its cognate sensor has not been identified. Here we show that AlgR is required for twitching motility, which is a form of bacterial surface translocation mediated by type 4 fimbriae. Adjacent to algR we have identified a sensor gene (fimS), which is also required for twitching motility. However, FimS does not appear to be required for alginate production in mucoid strains. FimS and AlgR are representative of a new subclass of two-component transmitter-receiver regulatory systems. The alternative sigma factor AlgU also affects both alginate production and twitching motility. Therefore, these two virulence determinants appear to be closely associated and coordinately regulated.